The impacts of farm work on health : Analyses of the hispanic health and nutrition examination survey - Guaranaccia, P. J.; Lowe, J. Angel; Angel, R.
tbls.
pp. 111-132
Keywords: Latinoamericanos; Estados Unidos de America; Salud; Trabajadores Agricolas; Migración Laboral